Cartilage acidic protein 1, a new member of the beta‐propeller protein family with amyloid propensity. Issue 2 (10th December 2016) - Anjos, Liliana; Morgado, Isabel; Guerreiro, Marta; Cardoso, João C. R.; Melo, Eduardo P.; Power, Deborah M.
ABSTRACT: Cartilage acidic protein1 (CRTAC1) is an extracellular matrix protein of chondrogenic tissue in humans and its presence in bacteria indicate it is of ancient origin. Structural modeling of piscine CRTAC1 reveals it belongs to the large family of beta‐propeller proteins that in mammals have been associated with diseases, including amyloid diseases such as Alzheimer's. In order to characterize the structure/function evolution of this new member of the beta‐propeller family we exploited the unique characteristics of piscine duplicate genes Crtac1a and Crtac1b and compared their structural and biochemical modifications with human recombinant CRTAC1. We demonstrate that CRTAC1 has a beta‐propeller structure that has been conserved during evolution and easily forms high molecular weight thermo‐stable aggregates. We reveal for the first time the propensity of CRTAC1 to form amyloid‐like structures, and hypothesize that the aggregating property of CRTAC1 may be related to its disease‐association. We further contribute to the general understating of CRTAC1's and beta‐propeller family evolution and function. Proteins 2017; 85:242–255. © 2016 Wiley Periodicals, Inc.